Do cash dividend increases from cessation of imputation tax system affect share prices in Malaysia? - Selamat, Aslam Izah; Syed Mohamed, Mohamed Ariff; Ramadilli Mohd, Shamsher Mohamad (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
Malaysia is among the first two countries to pass laws to abolish imputation tax system by replacing it with a simpler single tax system for corporate incomes. This paper provides evidence on how Bursa Malaysia shares responded to the announcement of the cessation of imputation tax system in 2007. Single tax regime is good news to shareholders as well as firms because this does away with firm’s need for reporting imputation credits. Shareholders too do not have to report dividend incomes any more. Despite the share price reactions in Bursa being clouded by the Global financial crisis impact at the same time as this tax law announcement, statistics show the market treated the event as good news with share prices significantly increasing on the first date of disclosure. As a robustness testing, we used another theory on ex-dividend day share prices. That test also confirms that the average dividend price drop ratio on ex-dividend days is statistically not different from 1.00 as predicted by theory because capital gains tax and personal tax are equal to zero on corporate incomes under the new tax.